Stalinist science - Krement͡sov, N. L. (Princeton, N.J. : Princeton University Press, 1997)
Some scholars have viewed the Soviet state and science as two monolithic entities--with bureaucrats as oppressors, and scientists as defenders of intellectual autonomy. Based on previously unknown documents from the archives of state and Communist Party agencies and of numerous scientific institutions, Stalinist Science shows that this picture is oversimplified. Even the reinstated Science Department within the Central Committee was staffed by a leading geneticist and others sympathetic to conventional science. In fact, a symbiosis of state bureaucrats and scientists established a much more terrifying system of control over the scientific community than any critic of Soviet totalitarianism had feared. Some scientists, on the other hand, developed more elaborate devices to avoid and exploit this control system than any advocate of academic freedom could have reasonably hoped. Nikolai Krementsov argues that the model of Stalinist science, already taking hold during the thirties, was reversed by the need for inter-Allied cooperation during World War II. Science, as a tool for winning the war and as a diplomatic and propaganda instrument, began to enjoy higher status, better funding, and relative autonomy. Even the reinstated Science Department within the Central Committee was staffed by a leading geneticist and others sympathetic to conventional science. However, the onset of the Cold War led to a campaign for eliminating such servility to the West. Then the Western links that had benefited genetics and other sciences during the war and through 1946 became a liability, and were used by Lysenko and others to turn back to the repressive past and to delegitimate whole research directions.
Frontmatter -- CONTENTS -- LIST OF FIGURES AND TABLES -- PREFACE -- LIST OF ABBREVIATIONS -- INTRODUCTION -- PART I: THE MAKING OF STALINIST SCIENCE -- Introduction -- CHAPTER 1. Russian Science in Transition, 1890-1929 -- CHAPTER 2. The Stalinization of Russian Science, 1929-1939 -- CHAPTER 3. Stalinist Science in Action: The Case of Genetics -- KEY EVENTS, 1917-1939 -- PART II: STALINIST SCIENCE IN THE 1940S -- Introduction -- CHAPTER 4. World War II and the Sweet Fruits of Victory -- CHAPTER 5. On the Threshold of the Cold War, 1946-1947 -- CHAPTER 6. The Fateful Year: 1948 -- KEY EVENTS, 1941-1953 -- PART III: THE CONSOLIDATION OF STALINIST SCIENCE -- Introduction -- CHAPTER 7. Talking the Talk: Ritual and Rhetoric -- CHAPTER 8. Walking the Walk: Education versus Research -- CHAPTER 9. The Realities of Stalinist Science: Careerism and Institutional Rivalry -- CONCLUSION -- APPENDIX A: Stalinist Scientific "Newspeak": A Glossary -- APPENDIX B: Key Figures -- NOTES -- NAME INDEX -- SUBJECT INDEX
Includes bibliographical references (pages 307-358) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Stalin, Joseph, -- 1878-1953.; Stalin, Joseph, -- 1879-1953.; Stalin, Joseph, -- 1878-1953; Science -- Soviet Union -- History -- 20th century; Soviet Union -- Politics and government -- 1936-1953.; Communism -- Soviet Union -- History -- 20th century; Sciences -- URSS -- Histoire -- 20e siècle.; URSS -- Politique et gouvernement -- 1936-1953.; Communisme -- URSS -- Histoire -- 20e siècle.; SCIENCE -- Philosophy & Social Aspects; Communism; Politics and government; Science; Soviet Union; 1900-1999; History